Efektivitas Standar Pelayanan Minimal (SPM) Dalam Penanganan Penyakit Tidak Menular (PTM) Di Uptd Puskesmas Citarik Kabupaten Sukabumi - Nuralita Anggini Futri; Dian Purwanti; Tuah Nur (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Minimum Service Standards (MSS) in the health sector are one of the national strategic programs, concerning provisions regarding the type and quality of basic services, including mandatory government affairs that every citizen is entitled to obtain at a minimum, so that performance achievements in fulfilling the quality of service of each type of basic service in the MSS in the health sector must be 100% every year. Citarik Public Health Center is one of the health centers that implement the MSS. The purpose of this study was to measure the effectiveness of SPM in handling non-communicable diseases (NCDs) at the health center. Based on initial observations, the achievement of NCDs health services in 2022 has not met the target. The implementation of MSS in handling NCDs at the Citarik Health Center has not been effective. This study used a qualitative research method with a descriptive approach. The theory used in this study is Duncan's theory of effectiveness with the measurement of three indicators, namely goal achievement, integration and adaptation. The results of this study indicate that MSS achievements in 2022 for services for Hypertension patients were 7.78% served according to standards, while for services for Diabetes Mellitus patients exceeded the specified target of 151% served according to standards. Socialization with community targets has not been carried out evenly and the quantity of Posbindu cadres has not been met. As a development of research related to MSS, it is expected to conduct further research related to MSS indicators that have not been researched.